2011
DOI: 10.1161/strokeaha.111.628586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-Hour Blood Pressure and Heart Rate Recorded With Ambulatory Blood Pressure Monitoring on Recovery From Acute Ischemic Stroke

Abstract: Background and Purpose-This study used ambulatory blood pressure (BP) monitoring to generate BP and heart rate (HR) profiles soon after stroke onset and evaluated the association between determined values and 3-month stroke outcomes. Methods-We analyzed 24-hour ambulatory BP monitoring records from 104 patients with acute ischemic stroke.Ambulatory BP monitoring was attached at the second and eighth hospitalization days (Days 1 and 7). Both BP and HR were characterized using baseline, mean, maximum, and minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 43 publications
(32 reference statements)
1
50
0
1
Order By: Relevance
“…5 Similarly, hour-to-hour BP variability during acute stroke also seems to predict stroke outcomes. 6 The present substudy of the Stroke Acute Management with Urgent Risk-factor Assessment and Improvement (SAMURAI) rt-PA Registry investigates associations between early BP variability during this period and outcomes of thrombolysis.…”
mentioning
confidence: 99%
“…5 Similarly, hour-to-hour BP variability during acute stroke also seems to predict stroke outcomes. 6 The present substudy of the Stroke Acute Management with Urgent Risk-factor Assessment and Improvement (SAMURAI) rt-PA Registry investigates associations between early BP variability during this period and outcomes of thrombolysis.…”
mentioning
confidence: 99%
“…As the INTERACT database only reports 90-day outcomes, we cannot make any conclusions about long-term mortality and morbidity. Although we recognize that there are several previous studies that showed significant association between heart rate variability (which may be a surrogate for an unfavorable sympathetic dysfunction) and clinical outcomes, 22,28,29 we were unable to analyze heart rate changes after admission because of lack of data. The use of admission heart rate may present some inevitable confounding factors, such as instrumental error from different batches of ECG monitor, discrepancy from reading of heart rate fluctuation, and the emotional status of patients at the point of measurement.…”
Section: Strokementioning
confidence: 94%
“…5,22 Higher heart rate might reflect patient distress and could be associated with other parameters such as higher and unstable blood pressure that have been reported to be related to hematoma growth during the clinical course. 23,24 In contrast to the main analyses, our subgroup analyses of patients with available 24-hour CT data (both with and without adjustment for hematoma growth) showed nonsignificant association between heart rate and 90-day mRS score.…”
Section: Figurementioning
confidence: 99%
“…Increased PP above a population norm has been associated with inferior outcomes in AIS [7] [8] [9] [10] [11], especially when PP exceeds 70 mmHg [7]. With the varying components of BP and the diversity of findings among the clinical trials of BP in AIS, the optimal approach to BP management in AIS remains unclear.…”
Section: Introductionmentioning
confidence: 99%